The use of CRF-41 in the differential diagnosis of Cushing's syndrome and obesity. - Grossman, A; Howlett, T; Kopelman, P (1987)
The use of a standard CRF test, using 100 micrograms i.v. synthetic ovine CRF-41, has been assessed in 22 patients with surgically-proven Cushing's disease and one patient with the ectopic ACTH syndrome secondary to a bronchial carcinoid. Three of the 22 patients, and the single patient with the ectopic ACTH syndrome, failed to produce a rise in serum cortisol to above the normal range in response to CRF-41. However, 18/22 patients with Cushing's disease had an enhanced cortisol response to CRF, including four patients who were resistant to high-dose dexamethasone. One patient with Cushing's disease responded to CRF-41 with an excessive cortisol response on one occasion, and a rise within the normal range on a second. Ten patients with simple obesity (mean weight 101 kg) were given CRF 0.5 microgram/kg, and their results compared to a control group of seven normal weight females (mean weight 58 kg). Peak serum cortisol responses to CRF were significantly less than in the control group, even when the dose was increased to 1 microgram/kg in six of the obese patients. Peak plasma ACTH responses were not significantly different between control and patient groups. It is concluded that the serum cortisol response to CRF is enhanced in the majority (but not all) of patients with Cushing's disease, and is attenuated in simple obesity. The reason for this attenuation requires further study.